Analisis Kesulitan Belajar Peserta Didik dalam Pembelajaran Aktif di Sekolah Dasar - Nadiyah Khairiyah; Khalis Salsabilla; Putri Akhriyani Siregar; Zulfa Zachri Wahyudi; Kartika Abriana Br Sembiring (Universitas Palan, 2024)
Each student has different abilities. There are students who can achieve it without difficulty, but quite a few students experience difficulties in learning. Several problems were found among students, such as laziness, easily discouraged, indifferent, accompanied by an attitude of opposition to teachers, which were part of students' learning problems. This article discusses the analysis of students' learning difficulties in active learning in elementary schools. The aim of this article is to gain a better understanding of what components influence students' ability to use active learning approaches in elementary schools optimally. The method used in this article is a qualitative method with a literature study approach. In reality, each student is often unable to achieve their learning goals or does not achieve changes in behavior as expected, this can indicate that students often experience learning difficulties and this is an obstacle in achieving learning outcomes at school. By knowing students' learning difficulties, they can of course identify and overcome these difficulties by looking for information about their learning problems, adjusting learning methods, providing additional support and using active learning strategies.